IMPACT OF PSYCHOLOGICAL STABILITY ON MANAGERS' ACTIVITIES - Tsvetelina Мihailova; Svetoslav Garov; Desislava Тоdorova; Todor Cherkezov (Peytchinski Publishing, 2016)
The latest research performed in European countries shows that the psychosocial risks and the job related stress will become more and more important in the years to come due to their increasing spread. These trends will have even greater influence on healthcare managers' activities due to the specific nature of their jobs, which, in turn, increases the needs of efficient leadership. The purpose of the questionnaire held is to study the impact of healthcare managers' psychological stability on the activities they perform in the course of their jobs. The analysis made shows that an individual's performance depends on their motivation, abilities and organizational conditions and skills. What is also found out is that people with different types of behavioral control work in healthcare operative management. People with different types of psychological stability will be needed for the different management levels.